2000
DOI: 10.1093/ajcn/71.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia: effects of exercise and restriction of energy intake compared

Abstract: The results suggest that the effect of exercise on postprandial lipid metabolism was greater than and different from that attributable to the energy deficit incurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
113
1
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 31 publications
9
113
1
8
Order By: Relevance
“…Previous data, reporting that the TG-lowering effect of an exercise-induced energy deficit was greater than that of an equivalent dietary-induced energy deficit, suggested either that the effects of exercise on postprandial TG metabolism were independent of an energy deficit, or that dietaryinduced and exercise-induced energy deficits elicited different effects on postprandial metabolism. 10 Data from the present study, showing that the TG-lowering effect of prior exercise was only evident with an accompanying energy deficit, suggest that the latter interpretation is the correct one. The contrasting effect on TG metabolism of a dietary-or exercise-induced energy deficit may be related to specific body tissues in which the energy deficits occur.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous data, reporting that the TG-lowering effect of an exercise-induced energy deficit was greater than that of an equivalent dietary-induced energy deficit, suggested either that the effects of exercise on postprandial TG metabolism were independent of an energy deficit, or that dietaryinduced and exercise-induced energy deficits elicited different effects on postprandial metabolism. 10 Data from the present study, showing that the TG-lowering effect of prior exercise was only evident with an accompanying energy deficit, suggest that the latter interpretation is the correct one. The contrasting effect on TG metabolism of a dietary-or exercise-induced energy deficit may be related to specific body tissues in which the energy deficits occur.…”
Section: Discussionsupporting
confidence: 56%
“…9 However, it has previously been shown that energy deficit is not the sole determinant of the exercise-induced changes in postprandial metabolism, as a dietary-induced energy deficit induces a smaller attenuation in postprandial TG concentrations than an equivalent exercise-induced deficit. 10 It remains unclear whether favourable effects of exercise on postprandial metabolism are still evident when there is an increase in energy intake to compensate for energy deficits caused by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first attempt to determine whether exercise can suppress the lipemic response to a meal approximating the macronutrient composition of the typical Western diet, that is (in terms of energy) 35-40% fat, about 47% carbohydrate, and about 16% protein (Williams, 2002). In fact, with the exception of Murphy et al (2000), who employed a diet providing 47% of energy from fat over the course of 1 day, all studies on the effect of exercise on postprandial lipemia have used test meals containing 60-93% of energy as fat, or 1.0-1.5 g/kg body mass (Maruhama et al, 1977;Schlierf et al, 1987;Klein et al, 1992;Aldred et al, 1994;Hardman & Aldred, 1995;Tsetsonis & Hardman, 1996a, b;Tsetsonis et al, 1997;Gill et al, 1998Gill et al, , 2001aGill et al, , b, 2002Hardman et al, 1998;Herd et al, 1998Herd et al, , 2000Herd et al, , 2001Zhang et al, 1998;Malkova et al, 1999;Gill & Hardman, 2000;Thomas et al, 2001;Petitt et al, 2003). Since the lipemic response to a fat meal is expected and has been shown to be positively related to the amount of fat ingested (Dubois et al, 1998), one could claim that exercise might not have a significant effect on lipemia after a meal of moderate fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been repeatedly shown to be effective to this end, especially when performed on the day before a fat-rich meal (Aldred et al, 1994;Tsetsonis & Hardman, 1996a, b;Tsetsonis et al, 1997;Gill et al, 1998Gill et al, , 2001aGill et al, , b, 2002Zhang et al, 1998;Malkova et al, 1999Malkova et al, , 2000Gill & Hardman, 2000;Herd et al, 2001;Thomas et al, 2001;Petitt et al, 2003). However, there does not seem to be a chronic effect extending beyond 2 days after the interruption of training Herd et al, 1998Herd et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation